Einfluss der Kreatin-Supplementierung auf die Leistungsfähigkeit bei repetitiver, hochintensiver Belastung - Koster, M. (Schweizerische Zeitschrift für Sportmedizin und Sporttraumatologie, 1996)
n a double-blind cross-over study with 10 trained male subjects, the effects of high doses of oral creatine supplementation on exercise performance were investigated. The test persons had to perform 10 sprinte of 6 seconds duration interrupted by 30 seconds rest periods on a cycle ergometer. From the 4th sprint on, the performance with creatine was significantly higher by about 5% in the 5th and 6th second of a sprint. The values for blood lactate were about 1 mmol/l lower from the 3rd sprint on. The body weight, however, was found to be increased by argund 1.4 kg. It could be shown that with creatine supplementation a possible slight enhancement of highly intensive, repetitive physical performance could be reached unlese it would be negatively influenced by the higher body weight.